Enzymatic removal of N-glycans by PNGase F coated magnetic microparticles - Bodnar, Judit; Szekrenyes, Akos; Szigeti, Marton; Jarvas, Gabor; Krenkova, Jana; Foret, Frantisek; Guttman, Andras (Electrophoresis, 2016)
Investigation of protein glycosylation is an important area in biomarker discovery and biopharmaceutical research. Alterations in protein N-glycosylation can be an indication of changes in pathological conditions in the medical field or production parameters of biotherapeutics. Rapid development of these disciplines calls for fast, high-throughput, and reproducible methods to analyze protein N-glycosylation. Currently used methods require either long deglycosylation times or large excess of enzymes. In this paper, we report on the use of PNGase F immobilization onto the surface of magnetic microparticles and their use in rapid and efficient removal of N-glycans from glycoproteins. The use of immobilized PNGase F also allowed reusability of the enzyme-coated beads as the magnetic microparticles can be readily partitioned from the sample by a magnet after each deglycosylation reaction. The efficiency and activity of the PNGase F coated magnetic beads was compared with in-solution enzyme reactions using standard glycoproteins possessing the major N-glycan types of neutral, high mannose, and highly sialylated carbohydrates. The PNGase F coated magnetic beads offered comparable deglycosylation level to the conventional in-solution based method in 10-min reaction times for the model glycoproteins of immunoglobulin G (mostly neutral carbohydrates), ribonuclease B (high mannose type sugars), and fetuin (highly sialylated oligosaccharides) with the special features of easy removal of the enzyme from the reaction mixture and reusability.
Keywords: glykoproteiny; Enzyme immobilization; Ribonucleases; ribonukleasy; PNGase F; glykopeptidasa; imunoglobulin G; Glycosylation; polysacharidy; Glycoproteins; Electrophoresis; Polysaccharides; Deglycosylation; elektroforéza; Immunoglobulin G; Oligosaccharides; oligosacharidy; Enzymes, Immobilized; Magnetic microparticles; glykosylace; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Microspheres; enzymy imobilizované; mikrosféry